2022
DOI: 10.1007/s13205-022-03334-9
|View full text |Cite
|
Sign up to set email alerts
|

Early diagnostic markers in predicting the severity of dengue disease

Abstract: The aim of the present study was to determine whether the serum ferritin, the biomarker of an acute phase reactant and the gall bladder wall edema, an early indicator of capillary leakage can predict the severity of dengue fever. This study included 131 patients, who were between the age group of 18–80 years. The patients presented to our department with an acute illness, within the first four days of high temperature. The statistical analysis of this study was performed by using the Chi-square and independent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 51 publications
0
7
0
1
Order By: Relevance
“…Loss of follow‐up and loss of the sample did not apply to the selected studies; therefore, study attrition was judged as low RoB for all papers (except one) by both raters. Overall, four studies were judged for a high RoB due to incomplete descriptions of key characteristics of study participants, study attrition, and study confounding measurement, 21,24,29,38 three had a moderate RoB, 19,32,52 and 11 studies were judged to have a low RoB (Figure 2). Both raters agreed on 84.26% of all the domains (90 out of 108).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Loss of follow‐up and loss of the sample did not apply to the selected studies; therefore, study attrition was judged as low RoB for all papers (except one) by both raters. Overall, four studies were judged for a high RoB due to incomplete descriptions of key characteristics of study participants, study attrition, and study confounding measurement, 21,24,29,38 three had a moderate RoB, 19,32,52 and 11 studies were judged to have a low RoB (Figure 2). Both raters agreed on 84.26% of all the domains (90 out of 108).…”
Section: Resultsmentioning
confidence: 99%
“…Participants 21,24,29,38 three had a moderate RoB, 19,32,52 and 11 studies were judged to have a low RoB (Figure 2). Both raters agreed on 84.26% of all the domains (90 out of 108).…”
Section: Picos Inclusion Exclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of this analysis indicate that while patients with both dengue shock and septic shock have evidence of pro-inflammatory hypercytokinaemia, there is a phenotypic difference between the inflammatory response in dengue shock (ferritin predominant) and septic shock (IL-6 predominant). Hyperferritinaemia has been reported as both a diagnostic and prognostic biomarker for dengue by several groups [12][13][14][15], but only one study has reported ferritin values quite as high as in our cohort; Kan et al found that mortality was twice as high in adults with severe dengue plus features of secondary haemophagocytic lymphohistiocytosis, compared to severe dengue alone [16]. Advancing this finding, we found that ferritin at enrolment was associated with mortality in a large group of adults with dengue shock, and that it was associated with other relevant clinical markers of disease severity such as SOFA score and requirement for ICU admission.…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%
“…Sangrado profuso que se considera clínicamente importante; 3. Compromiso grave de órganos (OMS, 2018;Moras et al, 2022). Definición de fiebre amarilla severa: Presencia de oliguria, algún signo de sangrado, bradicardia, insuficiencia hepática y renal, disfunción cerebral, convulsiones o coma (OMS, 2018;Oyono et al, 2022).…”
Section: Definición De Variablesunclassified